Role of Nucleoporins and Transport Receptors in Cell Differentiation - Khan, Asmat Ullah; Qu, Rongmei; Ouyang, Jun; Dai, Jingxing (Frontiers in Physiology, 2020)
Bidirectional molecular movements between nucleus and cytoplasm take place through nuclear pore complexes embedded in the nuclear membrane. These macromolecular structures are composed of several nucleoporins, which form seven different subcomplexes based on their biochemical affinity. These nucleoporins are the integral components of the complex, not only allowing passive transport but also interacting with importin, exportin, and other molecules that are required for transport of protein in various cellular process. Transport of different proteins are carried out either dependently or independently on transport receptors. As well as facilitating nucleocytoplasmic transport, nucleoporins also play an important role in cell differentiation possibly by their direct gene interaction. This review will cover the general role of nucleoporins (whether its dependent or independent) and nucleocytoplasmic transport receptors in cell differentiation.